“Without social there is no health”: Social work perspectives in multidisciplinary healthcare - Di Rosa, Roberta T. (Frontiers in Sociology, 2022)
The pandemic has not just affected the health sphere: strong social effects of the emergency have added to the health risk, stressing on social relations and the deterioration of people's living conditions, and making those who are already fragile more fragile. Notwithstanding, during the emergency following the COVID-19 pandemic the attention was focused, indeed understandably, on the health aspects, widening the already existing misalignment between the health interventions and the social ones. Emergency oriented efforts and resources more toward a clinical care approach (cure) than toward support for the social and the inclusion aspects (care). Reflecting on the specific area of health care that interacts with social care (and vice versa), shows how the medicalization in managing the emergency have undermined or, at least, weakened the global approach to the person and to vulnerability profiles that should inspire the socio-healthcare integration. The aim of this review is describing the relationship between the health and social systems and the effects of the COVID-19 pandemic on it: a review of studies on the role played by social work in the health sector before and during COVID-19 pandemic emergency shows how much potential there is still to be developed for social work in the health sector that acts together with the personal health services; a care that looks at the person within his or her relationships, community resources and environmental aspects requires an investment toward integration between hospital care, social services and local communities.